2009
DOI: 10.1007/s11595-009-5834-6
|View full text |Cite
|
Sign up to set email alerts
|

Solutionizing of additional ions in belite-rich clinkers and the properties of the resulting cement

Abstract: Belite-rich cement (BRC) can be made at lower temperature, but it has unsatisfactory reactivity. The crystal structure of dicalcium silicate (C 2 S) was modified by solutionizing some additional irons. By adding barium sulfate (BaSO 4 ) in the raw meals, the clinkers were easier to be burnt, and the compressive strength of BaSO 4 -modified BRC was considerably improved. The distortion of the crystal structure of C 2 S was confirmed by the interplanar distance change and nuclear magnetic resonance (NMR) of 29 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies shown that by adding mineralizer, the burning temperature can be reduced by 100℃ ~ 300℃, so as the energy consumption by 30%. Different ion-solid melting technology can reduce the sintering temperature, increase belite mineral content, and improve the belite hydration activity [8] .…”
Section: Applied Mechanics and Materials Vols 174-177mentioning
confidence: 99%
“…Studies shown that by adding mineralizer, the burning temperature can be reduced by 100℃ ~ 300℃, so as the energy consumption by 30%. Different ion-solid melting technology can reduce the sintering temperature, increase belite mineral content, and improve the belite hydration activity [8] .…”
Section: Applied Mechanics and Materials Vols 174-177mentioning
confidence: 99%
“…Cuesta et al [24] studied the activation mechanism of doped B 3+ ions on belite cement and found that Ca 2+ ions and Si 4+ ions in the [SiO 4 ] tetrahedron have been replaced, which contributes to the hydraulic reaction during cement hydration. Wang et al [25] studied the activation effect of BaSO 4 on β-C 2 S in belite cement clinker during calcination, and the results showed that BaSO 4 could dissolve into the crystal structure of β-C 2 S and improve the early compressive strength.…”
Section: Introductionmentioning
confidence: 99%